About the geometrical stability of the marginal terms in variation series - Aksomaitis, Algimantas (Lietuvos matematikos rinkinys, 2004)
It was proved that the logistic minimum is geometrically min-stable, positional statistics X(kN) , k > 1 are not geometrically stable, common minimum and maximum distributions are not asimptotically independent as the sample size is geometrical.